Hybrid Robotic Arm for Autonomous Aerial Refueling - Kaixuan Li; Gangfeng Liu; Yongsheng Gao; Jie Zhao (Chinese Journal of Mechanical Engineering)
Abstract Autonomous aerial refueling technology is gaining increasing attention to enhance aircraft combat capabilities. Current research on autonomous refueling focuses mainly on flight control laws, with little attention to the automation of refueling pipes. This leads to high demands on control law performance and navigation accuracy, making it difficult to ensure reliability. To address this, we propose a robotic arm system capable of automatic docking during the flexible aerial refueling process. The system uses a conical kinematic space configuration, offering enhanced stability and impact resistance. The frame-type structure achieves a lightweight design. Additionally, we establish a single-objective optimization model for the connecting rod dimensions and apply a genetic algorithm (GA) for their optimization. We also propose a trajectory-fitting calibration theory based on the robotic arm’s special configuration and complete its movement accuracy calibration using a laser tracker. This calibration method reduces the robotic arm’s motion error by 71%, achieving an absolute positioning accuracy better than 3.5 mm, which meets the requirements for autonomous aerial refueling. In summary, this research presents a hybrid robotic arm that meets automatic docking requirements, offering a new approach to autonomous aerial refueling.